2016
DOI: 10.1093/nar/gkw641
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryote-specific N-terminal extension of ribosomal protein S31 contributes to the assembly and function of 40S ribosomal subunits

Abstract: The archaea-/eukaryote-specific 40S-ribosomal-subunit protein S31 is expressed as an ubiquitin fusion protein in eukaryotes and consists of a conserved body and a eukaryote-specific N-terminal extension. In yeast, S31 is a practically essential protein, which is required for cytoplasmic 20S pre-rRNA maturation. Here, we have studied the role of the N-terminal extension of the yeast S31 protein. We show that deletion of this extension partially impairs cell growth and 40S subunit biogenesis and confers hypersen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 124 publications
2
30
0
Order By: Relevance
“…Experimental evidence indicates that while eS31 is a quasi‐essential r‐protein that assembles in the nucleus, most likely into early 90S pre‐ribosomal particles , eL40 is an essential r‐protein that associates in the cytoplasm with late pre‐60S r‐particles . Under wild‐type conditions, the Ubi1/2 and Ubi3 precursor proteins could so far never be detected, suggesting that their proteolytic maturation occurs very rapidly, likely co‐translationally, and therefore before the assembly of the respective r‐proteins into pre‐ribosomal particles . In agreement, the ubiquitin moiety of the Ubi1/2 and Ubi3 precursors can be deleted without causing a deleterious phenotype as long as the unfused r‐proteins are expressed at elevated dosage (, and our unpublished results).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Experimental evidence indicates that while eS31 is a quasi‐essential r‐protein that assembles in the nucleus, most likely into early 90S pre‐ribosomal particles , eL40 is an essential r‐protein that associates in the cytoplasm with late pre‐60S r‐particles . Under wild‐type conditions, the Ubi1/2 and Ubi3 precursor proteins could so far never be detected, suggesting that their proteolytic maturation occurs very rapidly, likely co‐translationally, and therefore before the assembly of the respective r‐proteins into pre‐ribosomal particles . In agreement, the ubiquitin moiety of the Ubi1/2 and Ubi3 precursors can be deleted without causing a deleterious phenotype as long as the unfused r‐proteins are expressed at elevated dosage (, and our unpublished results).…”
Section: Introductionmentioning
confidence: 66%
“…In contrast to this role as a chaperone, an active contribution of the ubiquitin moiety to ribosome biogenesis prior to cleavage is controversial and likely negligible. We have previously demonstrated that assembly of eS31 and eL40 into pre‐ribosomal particles preferentially occurs in the nucleus and the cytoplasm respectively . However, in no circumstance either the wild‐type Ubi3 or Ubi1/2 fusion precursors could be detected by western blot, suggesting that the processing of the precursors into ubiquitin and the respective r‐protein occurs very rapidly, possibly even co‐translationally, and as a corollary before their assembly into the respective pre‐ribosomal particles.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The characterization of these proteins, which have no counterparts in bacterial ribosomes, was precluded from recently reported structures of Leishmania and other eukaryotes due to their high mobility in the absence of an A-site tRNA and PAR 13 , 20 , 21 . Recent studies in yeast showed that mutations of eS30 and eL41 homologs confer hypersensitivity to AGs 22 , 23 , suggesting that these proteins may play a role in the organization of the PAR-binding pocket and in eukaryote decoding. These results correlate with our observations that the two proteins maintain tight interactions with several binding pocket elements known to be crucial for decoding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These sequences vary strikingly across species. Using the S. cerevisiae system, functions of some of the eukaryote-specific extensions/insertions have been explored (e.g., see [51][52][53][54][55][56][57][58][59][60]). These studies have revealed a collection of functions: harboring nuclear localization signal, rRNA processing, subunit assembly and recruiting certain translational components ( [54] and reference therein).…”
Section: Species-specific Roles Of Eukaryotic Ribosomal Protein Extenmentioning
confidence: 99%